Communication in soccer: from reserve on the bench to first-team forward - Figueiredo, Diego; Albino, José Coelho de Andrade (Organicom, 2011)
This article shows the results of a survey conducted with the purpose of understanding the process of projection of the corporative identity of Sport Club Internacional, of Porto Alegre (RS). It mainly addresses the way that the organization seeks to reconcile the ambiguity of the club and enterprise labels, principally in the projection of its identity in the “Alma colorada” (Crimson soul) advertising campaign. The study combines the concepts of vision, culture in organizations, identity and image, by addressing communication under the optics of cultural studies and of cultural semiotics. Thus, it concerns a qualitative survey of a descriptive nature that uses the case study method.